(untitled) (Research, Society and Development, 2022)
Cracids represent one of the most threatened groups of birds in Latin America, in which more than a third of the species are in danger of extinction, especially the bare-faced curassow (Crax fasciolata), classified as critically endangered in the State of Sao Paulo. In this context, measures are necessary to guarantee its conservation, such as the evaluation of areas with occurrence of the species, as well as the conservation of the last remnants of semideciduous forest in the State. Thus, this article aims to present the records of specimens of the Crax fasciolata species, obtained through photographic trapping, in the year 2019, in a Municipal Conservation Unit located in the urban area of ​​the municipality of Franca, São Paulo. Four specimens were visualized, three females and one male, in an area of ​​Semideciduous Seasonal Forest. Thus, it is concluded that the protected area is characterized as a favorable environment for the survival of the species, pointing out the extreme importance of the Conservation Unit.